Which Is More Important for Health: Sleep Quantity or Sleep Quality? - Jun Kohyama (MDPI AG, 2021)
Sleep is one of the basic physiological processes for human survival. Both sleep quantity and sleep quality are fundamental components of sleep. This review looks at both sleep quantity and sleep quality, considering how to manage the complex but probably unavoidable physiological phenomenon of sleep. The need for sleep has marked variations between individuals, in addition to the effects of variable conditions. Studies on sleep quality started later than those on sleep quantity, beginning in 1989 when Ford and Kamerow revealed that insomnia increases the risk of psychiatric disorders. According to the nationwide research team on the quality of sleep (19FA0901), sleep quality is superior to sleep quantity as an index for assessing sleep, and that restfulness obtained through sleep is a useful index for assessing sleep quality. We should pay more attention to obtaining sleep of good quality (restfulness, no sleepiness, no need for more sleep, sufficient objective sleep depth, etc.), although there have not been enough studies on the associations between sleep quality and health or disorders in children and adolescents. Further studies using the deviation from an individual's optimal sleep quantity may show us another aspect of the effects of sleep quantity on various life issues.